Превентивний механізм сучасного права - Батан, Юрій (My University, 2021)
Дисертацію присвячено комплексному дослідженню превентивного механізму сучасного права та з’ясуванню його ознак і складників, а також напрацюванню запобіжно-спрямованих змін до правових актів. Піддано комплексному аналізу історіографію юридичної превенції. Розкрито методологічні засади дослідження превентивного механізму сучасного права. Здійснено поділ превентивного механізму сучасного права. Досліджено телеологічний елемент превентивного механізму сучасного права. Продемонстровано нормативний елемент превентивного механізму сучасного права. Обґрунтовано недоцільність ухвалення окремого Закону України «Про профілактику правопорушень» або аналогічного до нього законодавчого акта, що б мав на меті врегулювати засади профілактики правопорушень (злочинів, злочинності тощо). Окреслено суб’єктний елемент превентивного механізму сучасного права. Обґрунтовано концепцію верховенства права як основу превенції порушень прав людини. Досліджено концепцію стабільності законодавства як складник верховенства права та запобіжник порушень прав людини. Виявлено сучасні проблеми ефективності превентивного механізму сучасного права.

The thesis is devoted to a comprehensive study of the preventive mechanism of modern law, clarification of its features and components and the development of preventive-oriented changes to legal acts. The historiography of legal prevention is comprehensively analyzing, making possible to identify approaches, directions and gaps of doctrinal research on the preventive mechanism of modern law. Certain approaches to legal research of prevention are highlighted: general theoretical approach, criminal law-based approach, public and private law approaches. Each approach is divided into the following areas of research: the preventive function (subfunction) of law (in the whole or in the certain legal communities respectively); prevention of conflicts; preventive function of legal responsibility; preventive activities of the internal affairs agencies (in private law – preventive activities of the notaries). Preventive mechanism of modern law is examined on methodological framework, namely a preventive-teleological researching approach is formulated. According to the author, it consists of the consideration of norms, institutions, subjects, sources of law, legal concepts, legal acts, etc. through the prism of their preventive purpose. In terms of this approach, individual subjects (mediators, legal clinics, ombudsperson, etc.) and concepts (rule of law, constitutionalism, good governance, sustainable development) are considered. The division of the preventive mechanism of modern law was carried out. This mechanism consists of system and structural components. The system component has at least six main criteria for division: functions, limits and scale of influence, stages, object, subject and legal regime, subjects. The structural component of prevention consists of teleological, normative, subjective and value-dynamic elements. The teleological element of the preventive mechanism of modern law was reviewed. It has been found that prevention is not a subfunction or function, but the main (ultimate) purpose of objective law, which consists of identifying, eliminating, reducing the level and scale or decrease the impact of the determinants of human rights violations. Because of this, the implementation of the preventive purpose of the law as a mechanism, i.e. a dynamic system taken in the unity of an orderly integrated set of interrelated legal means, methods and procedures used by participants of public relations, authorized by the regulators, enforcing the desire to achieve the rule of law, anthropocentrism, constitutionalism, good governance, sustainable development, etc., and aimed at identifying, eliminating, reducing and scaling up or mitigating the impact of determinants of human rights violations was described. Based on this understanding of prevention, the thesis of the division of normative acts into those that have a preventive purpose and those that do not, and the division of measures into preventive and coercive was refuted. The normative element of the preventive mechanism of modern law was demonstrated. Based on the comparative legal analysis of the content of foreign laws on crime prevention, historical and legal analysis of submission and consideration of domestic law drafts on crime prevention, as well as the application of the formally-legal method, the inexpediency of adopting a separate Law of Ukraine “On Crime Prevention” or similar act of legislation aimed at regulating the principles of crime prevention (crimes, criminality, etc.) was proved. The subjective element of the preventive mechanism of modern law is outlined. It is proposed to divide the system of subjects of prevention into four types: ideological (educational and cultural institutions, mass media), legislatory (the parliament, international organizations and their bodies, head of state, the government, local self-government bodies), legally assisting (advocacy, legal clinics, non-governmental human rights institutions, mediators, natural persons, public and economic management bodies, labor collectives), control-supervisory (international human rights treaty bodies, the notary, registrators, the Ombudsman, national preventive mechanism, state inspections, courts, the Constitutional Court, arbitrations, public organizations, legal departments of institutions, the Ministry of Justice of Ukraine, law enforcement agencies). The concept of the rule of law as a basis for the prevention of human rights violations is justified. To interpret this concept in terms of an element-by-element approach, which includes the following components: respect for human rights, legal certainty, proportionality, non-discrimination, the right to be heard, the right to appeal and accountability was proposed. The concept of stability of legislation as a component of the rule of law and a safeguard against human rights violations was examined. The stability of legislation means its ability to regulate public relations without significant changes over a long period in compliance with “legitimate expectations”. According to the results of the study, the need to complement the Chapter II of the Constitution of Ukraine “Human and Citizens’ Rights, Freedoms and Duties” (after the current Part 1 of Article 38) with the norms of the stability of electoral legislation of the following content: “Changes to the election legislation regarding votes in the mandates, the conduct of the boundaries of districts and the procedure of forming election commissions shall come into force not earlier than two hundred and forty days after their promulgation”. Modern problems of efficiency of the preventive mechanism of modern law are revealed. It was found that the use of statistics in the analysis of preventive activities is based on the number of offences. It is established that the statistical method has a much greater potential for its use in legal research: there are many indicators of inflation in the socio-humanitarian sphere, the effectiveness of control and supervision, prevention of violations of the right to be heard, prevention of unavailability of business. The survey indicators of the effectiveness of modern law are conditionally divided into four types: material rule-making, material law-enforcement, procedural rule-making, procedural law-enforcement
діс. к.ю.н. 12.00.01
Батан Ю. Д. Превентивний механізм сучасного права : дис. … канд. юрид. наук : 12.00.01 / Батан Юрій Дмитрович. – Одеса, 2021. – 267 с.
Keywords: методологія права; превентивна функція права; превентивна мета правового регулювання (впливу); закон про профілактику правопорушень; структура механізму превенції порушень прав людини; суб’єкти запобігання порушенням прав людини; верховенство права; стабільність законодавства; ефективність механізму реалізації превентивного призначення права; індикатори ефективності запобігання правопорушенням; methodology of law; preventive functions of law; the preventive aim of legal regulation (impact); the prevention of delinquency law; structure of the mechanism of prevention of human rights violation; subjects of prevention of human rights violations; the rule of law; stability of the legislation; the effectiveness of the mechanism for implementation of the preventive purpose of the law; indicators of the effectiveness of crime prevention